La asociatividad económica de pequeñas unidades productivas y la agroexportación en la macro región nor oriental del Perú - Querevalú Morante, Carlos Alberto (2008)
In this research work it has been examined the levels of organization, management capacity and the development of the economic associativity of small productive units and the agricultural exports in the “macro region” the north of Peru; assess if they are include successful in exporting channels in a cost-effective and economically equitable and sustainable growth over time. The different successful experiences of productive chains and asociability have been analyzed in many organizations like as: “Asociación de Productores Agrícolas de Rodriguez de Mendoza” - APARM, “Cooperativa Agraria Cafetalera Bagua Grande” - CACBG, “Asociación de Productores Ecológicos – APROECO, “Asociación de Pequeños Productores de Banano Orgánico de Saman y Anexos” – APPBOSA, “Asociación de Pequeños Productores de Banano Orgánico de Valle del Chira” – APROBOVCHIRA, “Asociación de Pequeños Productores de Tongorrape” - APPT. By means of surveys interview, field work, It has been evaluated the main factors of the economic associability and its relation with the agricultural export. It was found that there is a direct relation between the levels of economic associability, the economic and social development, and the protection to the environment in the zones of influence of the small productive units, due to the fact that the small production unit received directly from final consumer a surcharge (28%) against a cost of certifications demanded in the economic associability, which amounted is the 5 % .of commercialization price of individual way. The certificate companies demand that the surcharges will be invested to fulfill norms that allow living together with the environment harmonious and to improve quality of life of the small productive units in a sustainable manner.